2022
DOI: 10.1177/03000605221121965
|View full text |Cite
|
Sign up to set email alerts
|

A fatal case of chlorfenapyr poisoning and a review of the literature

Abstract: Background Chlorfenapyr is a widely used pesticide and is classified as moderately hazardous to human health. Ingestion usually leads to mortality in humans. However, chlorfenapyr toxicity has a variable course and mechanism of action. Case presentation: We report the case of a 79-year-old female who ingested chlorfenapyr with the intent to commit suicide. The liquid was ingested 2 hours before she was brought to our emergency department. Gastric lavage was immediately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 13 publications
(42 reference statements)
1
5
0
Order By: Relevance
“…Another similar radiology features reported by Kang et al [11] also indicated that low white matter density in whole brain tissue with CT scan. In a preceding animal experiment in rats, vacuolar myelopathy and mild myelin sheath swelling were found in a variety of structures ranging from subcortical areas to the brainstem and spinal cord in neuro histopathological examination with chlorfenapyr poisoning [15], which is consistent with MRI ndings in clinical case reports. The pathophysiology under the susceptibility of the white matter tracts alone is unknown.…”
Section: Discussionsupporting
confidence: 82%
“…Another similar radiology features reported by Kang et al [11] also indicated that low white matter density in whole brain tissue with CT scan. In a preceding animal experiment in rats, vacuolar myelopathy and mild myelin sheath swelling were found in a variety of structures ranging from subcortical areas to the brainstem and spinal cord in neuro histopathological examination with chlorfenapyr poisoning [15], which is consistent with MRI ndings in clinical case reports. The pathophysiology under the susceptibility of the white matter tracts alone is unknown.…”
Section: Discussionsupporting
confidence: 82%
“…This suggested that chlorfenapyr could diminish the antioxidant capacity and induce oxidative stress of the mice liver, which was confirmed by HepG2 cells. Similarly, a study on mice showed that chlorfenapyr can induce DNA damage in liver cells. , Furthermore, a fatal case of chlorfenapyr poisoning in humans revealed elevated liver enzyme levels and damage to the liver . Typically, oxidative stress promotes membrane lipid peroxidation, alters biological membrane functionality, covalently binds to biomacromolecules, impairs enzyme activity, and induces various degrees of liver damage under the influence of nuclear factor-κB (NF-κB). , Similarly, serum metabolomics showed that chlorfenapyr induced the expression of NF-κB factors in mice serum.…”
Section: Discussionmentioning
confidence: 99%
“…18,20 Furthermore, a fatal case of chlorfenapyr poisoning in humans revealed elevated liver enzyme levels and damage to the liver. 45 Typically, oxidative stress promotes membrane lipid peroxidation, alters biological membrane functionality, covalently binds to biomacromolecules, impairs enzyme activity, and induces various degrees of liver damage under the influence of nuclear factor-κB (NF-κB). 46,47 Similarly, serum metabolomics showed that chlorfenapyr induced the expression of NF-κB factors in mice serum.…”
Section: Chlorfenapyr Induced Hepatotoxicitymentioning
confidence: 99%
“…In animals, dealkylation of an ethoxymethyl group on chlorfenapyr, reveals the active metabolite, tralopyril, which uncouples mitochondrial oxidative phosphorylation to disrupt ATP-production leading to death [37]. Although relatively non-toxic to HEK293 cells (EC 50 = 20.918 ± 7.337 µM), there have been poisoning cases with chlorfenapyr [38, 39, 40], likely undermining its direct repurposing potential as an anthelmintic.…”
Section: Discussionmentioning
confidence: 99%